Impact of Migration on Language: The Case of Curaçao - Goede, Miguel (Archives of Business Research, 2023)
Purpose: The purpose of this article is to analyze the influence of migration on the Papiamento language in Curaçao. Methodology: The paper draws from published articles and reports on migration, data from the Bureau of Statistics, and interviews with key informants. Findings: Although the position of Papiamento has changed, the magnitude of this change and the reasons behind it are difficult to determine due to the lack of official data. Originality: The article is part of a larger body of work addressing this phenomenon. The evidence provided in Small States & Territories offers a valuable perspective on the impact of migration on language. Conclusions: Although the position of Papiamento language has experienced fluctuations in the past, it remains very strong and is value to Curaçao community is expected to remain stable. Paper type: Inventory study